Double flap from amputated opposite lower limb for cover of plantar and dorsal surfaces of a crushed foot - Kumta Samir; Purohit Shrirang; Chitranshi Anurag (Indian Journal of Plastic Surgery)
Bilateral limb trauma poses many possibilities for management. In a situation of bilateral amputation, if the amputated limb is not salvageable or replantation is not advisable, the amputated limb can be used to harvest tissue for free tissue transfer to cover the amputation stump. We describe a case here in which we have used these principles.